Conference Report: Summer in the City. Different Aspects of Culture [Lato v mieście. Różne oblicza kultury]: 25th–26th June 2009, Krakow, Poland. - Novotná, Hedvika (Lidé města, 2009)
Another of the series of conferences devoted to urban ethnology/anthropology took place in Polish Krakow in June. It was organized by the Polish Academy of Sciences, the Institute of Archaeology and Ethnology, Department of Ethnology; the Polish Academy of Arts and Sciences; the Polish Academy of Sciences, Committee on Ethnological Sciences, the Committee for Urban Anthropology and the Polish Society of Urban Ethnology. This time, a seemingly light topic was chosen by the organizers: Summer in the City.